Recent Advances in the Management of Atrophic Tibial Non-Unions; An update using Extra Corporeal Shock Wave Therapy - Umair Abu Bakar Siddiq, Mirza Zeeshan Sikandar, Saqib Javaid Ahmad, Muhammad Salman Khalil Uppal, Amir Manzoor, Mariya Tahir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Tibial nonunion remains a significant clinical challenge despite advances in surgical management. New techniques to help manage tibial nonunion include extracorporeal shock wave therapy and percutaneous application of bone marrow aspirate. Management strategies vary based on the type of nonunion: aseptic or infected, and atrophic or hypertrophic. Extracorporeal shock wave therapy has been shown to be as effective as surgical management in patients with stable hypertrophic nonunion. Objective: To determine the efficacy of extracorporeal shock wave therapy for aseptic non-union of the tibia Methodology: A randomized controlled trail was conducted at Orthopedic Emergency department Central Park Teaching Hospital from March 2022 to November 2022. Results: In our study, out of 120 cases, 52.5%(n=63) were between 15-40 years and 47.5%(n=57) were between 41-60 years of age, mean + sd was calculated as 41.22+7.17 years, 60.83%(n=73) male and 39.17%(n=47) females. Frequency of efficacy of extracorporeal shock wave therapy for aseptic non-union of the tibia revealed in 86.67%(n=104). Practical Implication ESWT therapy can be used as non-invasive method of treating non-healing fractures of tibia without compromising the surgical anatomy. Conclusion: We concluded that the frequency of efficacy of extracorporeal shock wave therapy for non-union of the tibia is significantly higher and the patients treated with this technique may have a benefit of non-operative procedure. Keywords: Aseptic non-union of the tibia, extracorporeal shock wave therapy, efficacy